Endothelial cell regulation of leukocyte infiltration in inflammatory tissues - A. Duperray; A. Mantovani; M. Introna; E. Dejana (Mediators of Inflammation)
Endothelial cells play an important, active role in the onset and regulation of inflammatory and immune reactions. Through the production of chemokines they attract leukocytes and activate their adhesive receptors. This leads to the anchorage of leukocytes to the adhesive molecules expressed on the endothelial surface. Leukocyte adhesion to endothelial cells is frequently followed by their extravasation. The mechanisms which regulate the passage of leukocytes through endothelial clefts remain to be clarified. Many indirect data suggest that leukocytes might transfer signals to endothelial cells both through the release of active agents and adhesion to the endothelial cell surface. Adhesive molecules (such as PECAM) on the endothelial cell surface might also ‘direct’ leukocytes through the intercellular junction by haptotaxis. The information available on the molecular structure and functional properties of endothelial chemokines, adhesive molecules or junction organization is still fragmentary. Further work is needed to clarify how they interplay in regulating leukocyte infiltration into tissues.